Evaluasi status kesuburan tanah didesa nglegi, kecamatan patuk, kabupaten gunungkidul, daerah istimewa yogyakarta - Andi Suseno; Dyah Arbiwati; AZ Purwono Budi Santosa (Universitas Pembangunan Nasional Veteran Yogyakarta, 2018)
Evaluation of Soil Fertility Status in Nglegi Village, Patuk Sub-District, Gunungkidul District (Andi Suseno, Dyah Arbiwati, and AZ Purwono Budi Santosa): Nglegi Village has relatively good potential in the fields of agriculture, plantations and animal husbandry, and contributes as a food supply supplier to the areas in Patuk Subdistrict and its surroundings.Based on data from the Department of Agriculture and Food of the last 5 years in the Gunungkidul region, Nglegi Village is a producer of food crops such as cassava, rice and soybean, the second largest after Paliyan District. Thus this region is a producer of food crops in the District of Patuk.This studyaims to evaluate the soil fertility status, find out the obstacles and overcome problems and make a soil fertility map in Nglegi Village, Patuk District, Gunungkidul Regency. This study uses a survey method to describe the general condition of the area and the determination of sample points based on the Land Map Unit made by overlaying the land use map, and the slope map. Assessment of soil fertility status based on a combination of several parameters of soil chemical properties (PPT 1983).The results showed that there were two fertility statuses namely moderate and low fertility status. Fertility limiting factors are C-Organic and low Nitrogen levels. Giving organic material and fertilizers containing Nitrogen is one of the alternatives for solving this problem.soil Fertility status; Nglegi village